NAVIGATING POLITICAL SILENCE: THE IMPACT OF TWITTER BAN ON NIGERIAN YOUTH ACTIVISM - Ifeduba, Emmanuel; Temitope Koyi, Olubusayo; Olatundun Jire-Oladiran, Grace (African Journal of Social and Behavioural Sciences, 2024)
Twitter has emerged as a vital forum for political activism and conversation, particularly among young people. It is an effective instrument for political engagement because of its capacity to promote quick information sharing, rally supporters, and magnify voices. The consequences of this ban on political participation and communication have been significant. It was extremely difficult for political movements that depended on the platform for coordination and communication to stay visible and gain traction. It is a potent social media tool that has transformed social interaction, communication, and information sharing across a range of industries, including politics, entertainment, news, and private messaging. The study aims to explore how youth activism and political participation have been affected by the ban, as well as how they adapt and discover new ways to mobilise support and express their political beliefs. The methodology of this study was gathered through primary data collection. The key findings of the study are that the bans on Twitter led to a significant decline in political participation among young people. In the absence of Twitter, young people are adopting a variety of innovative approaches and techniques for political activism. This study concludes that while censorship may inadvertently foster creativity and resilience in activists, pushing them to develop new strategies, the implications of this kind of ban are profound. The study recommends that to sustain youths’ political engagement despite challenges posed by Twitter restriction; society must go back to the traditional route: an offline community-building effort where youths can engage in discussions like town hall meetings and face-to-face interactions with grassroots leaders like the Local Government Chairman to mitigate the effects of the banned online space.